PENERAPAN METODE BAYES DALAM MENGESTIMASI PREMI KREDIBILITAS PADA ASURANSI UMUM - BANGUN, RAIN FERNANDO; WIDANA, I NYOMAN; NILAKUSMAWATI, DESAK PUTU EKA (E-Jurnal Matematika; Vol 10 No 4 (2021), 2021)
Determination of insurance premiums is very important the calculation must be done carefully so that there is experience losses . The purpose of this research is to find out the application of empirical Bayes credibility theory Model 1 and estimate of the credibility premium on general insurance . A method that can help in overcoming these problems, that is empirical Bayes credibility theory Model 1, results of the estimated credibility premium credibility (in Euros) for insurance companies Alianz, Csob, Generali, Koop, Unisqa, and Wusten respectively as follows: 46.774811, 7.801307, 10.368991, 58.812250, 6.703035, and 5.091605.   These results, the average claim is greater than the credibility premium, so that insurance companies can reserve premiums for the future .